2022
DOI: 10.1111/asj.13708
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 improves the quality of sheep sperm stored at room temperature by mitigating oxidative stress

Abstract: The purpose of this experiment was to explore whether coenzyme Q10 (CoQ10) improves the quality of sheep semen stored at room temperature by attenuating oxidative stress. Semen was diluted without (control group), and with antioxidants (5, 50, 250, and 500 μmol/L CoQ10). Sperm kinetic parameters and plasma membrane integrity were determined, and the reactive oxygen species (ROS), malondialdehyde (MDA), adenosine triphosphate (ATP), mitochondrial membrane potential (MMP), total antioxidant capacity (TAOC), cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The results showed that the 45 µM group of punicalagin decreased the plasma membrane integrity, acrosome integrity and MMP of sperm compared to the 30 µM group. The 45 µM group may have altered the permeability of the mitochondrial membrane, leading to the release of Cytochrome C from sperm, which affected mitochondrial function and sperm motility [37]. The results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the 45 µM group of punicalagin decreased the plasma membrane integrity, acrosome integrity and MMP of sperm compared to the 30 µM group. The 45 µM group may have altered the permeability of the mitochondrial membrane, leading to the release of Cytochrome C from sperm, which affected mitochondrial function and sperm motility [37]. The results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Appropriate level of ROS play a crucial role in spermatozoa capacitation, acrosome reaction, and the preservation of cell membrane fluidity 41 , 42 . However, when the level of ROS exceeds a certain threshold, it can have a detrimental effect, leading to oxidative stress and damage to spermatozoa 43 . In this study, the level of ROS in post-thawed spermatozoa in the 2 cm fumigation group for 20 min was significantly lower than that in the 6 and 8 cm groups.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [94] used a commercial kit (Beyotime Institute of Biotechnology, Shanghai, China) to determine ROS content in ram semen (2.0 × 10 9 /mL), using DCFH-DC as a probe. The fluorescence intensity was monitored using a multifunctional microplate reader (PerkinElmer Inc., NYSE: PKI, Waltham, MA, USA) at Ex/Em = 488/525 nm).…”
Section: Ros Assay In Spermatozoamentioning
confidence: 99%
“…Wang et al [94] used a WST-8 kit (Beyotime Institute of Biotechnology, Shanghai, China) for measuring SOD activity in ram. Samples of semen (2.0 × 10 9 /mL) were centrifuged at 12,000× g for 5 min, and after incubation with WST-8/enzyme working solution, the absorbance at 450 nm was determined.…”
Section: Sod In Spermatozoamentioning
confidence: 99%